Islamic educational system in Kelantan, Malaysia: traditional and modern approaches - Nor, M.R.M.; Ibrahim, A.Z.B.; Hamid, F.A.F.A.; Jalani, H.; Ramli, M.F.M.; Yusof, A.; Halim, A.A.; Latif, F.A. (IDOSI, 2012)
Islamic Education in Malaysia began as an informal institution in its early days. This is because of the nature of development during those times, where some places such as surau, mosque and madrasah became centre for teaching the aspects of the religion. The system develops gradually, from informal to a formal system which has changed the style of learning. Nevertheless, the informal system is still existed even until today, along with the formal educational system. This is especially in Kelantan, where it becomes clear that both institutions are still running concurrently. In this paper, the authors aim to examine and analyse the Islamic Educational system in Kelantan as it is a unique experience for such a state to keep traditional institution running in this day. This paper will also discuss the development of the formal system that is established for educating the religion to the people.